2014
DOI: 10.1007/s10393-014-0972-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathological Findings in Green Turtles (Chelonia mydas) from Gladstone, Queensland: Investigations of a Stranding Epidemic

Abstract: An investigation into the health of green turtles was undertaken near Gladstone, Queensland, in response to a dramatic increase in stranding numbers in the first half of 2011. A total of 56 live turtles were subject to clinical examination and blood sampling for routine blood profiles, and 12 deceased turtles underwent a thorough necropsy examination. This population of green turtles was found to be in poor body condition and a range of infectious and non-infectious conditions were identified in the unhealthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 19 publications
2
46
0
Order By: Relevance
“…127! were emaciated during the flood event (Flint et al, 2014). The measured protein content fell well within the range of previously reported values (Table S2) .…”
Section: Section S1 Theoretical Considerations Of K Pdms-bloodsupporting
confidence: 89%
“…127! were emaciated during the flood event (Flint et al, 2014). The measured protein content fell well within the range of previously reported values (Table S2) .…”
Section: Section S1 Theoretical Considerations Of K Pdms-bloodsupporting
confidence: 89%
“…Their high affinity for coastal habitats, reliance on both marine and terrestrial environments, and long life span make them ideal candidates to act as sentinel species (Aguirre and Lutz, 2004). The occurrence and prevalence of diseases in sea turtles in many cases is likely to be linked to the health of marine habitats (Aguirre and Lutz, 2004;Flint et al, 2015b;Harvell et al, 1999;Jacobson et al, 2006;Ward and Lafferty, 2004).…”
Section: Figure 52mentioning
confidence: 99%
“…Other indirect threatening processes include degradation of feeding and nesting habitats and water quality decline associated with industry and agriculture. A recent assessment of turtle health in the Gladstone (central Queensland) region, in response to a spike in strandings, concluded that the general poor population health observed was likely attributable to a combination of extreme weather (flooding) and previously existing environmental stressors (Flint et al, 2015b).…”
Section: Anthropomorphic Threatsmentioning
confidence: 99%
See 2 more Smart Citations